The influence of Social Media Use of older adults on the Exercise Habits: The chain mediating effects of active coping strategies and perceived social support - Qiu Jie; Mengfen Liu; Jiawei Chen; Jianhua Zhang; Shaokai Tang; Zeng Zhou (PLoS ONE, 2026)
With the advancement of internet adaptation for the older adults, social media has increasingly become an important platform for older adults to access health information and maintain social connections. At the same time, older adults’ Social Media Use behavior has a unique impact on the development and maintenance of their Exercise Habits. Methods To explore the mechanisms through which Social Media Use affects older adults’ Exercise Habits, a cross-sectional design was employed. A convenience sampling method was used to select 1,119 individuals aged 60 and above. Social Media Use, Exercise Habits, Active Coping Strategies, and Perceived Social Support Scales were used for the survey, and the mediating roles of Active Coping Strategies and Perceived Social Support in the relationship between the two were analyzed. Results Social Media Use significantly positively influenced older adults’ Active Coping Strategies and Perceived Social Support. Furthermore, Active Coping Strategies and Perceived Social Support each had a significant positive impact on older adults’ Exercise Habits. Notably, Social Media Use exerted a significant positive indirect effect on Exercise Habits through the chain path of Active Coping Strategies → Perceived Social Support. Conclusion The impact of Social Media Use on older adults’ Exercise Habits does not occur directly, but rather through a psychological chain, involving the acquisition of age-appropriate exercise resources, the formation of Active Coping Strategies, the perception of diverse social support, and the consolidation of Exercise Habits. This provides a theoretical basis and practical guidance for promoting healthy behaviors in older adults through social media interventions.